+0  
 
+1
32
1
avatar+133 

Help

 Mar 18, 2020
 #1
avatar+18926 
0

Verify:  cos(x) + cos(x)·cot2(x)  =  cot(x)·csc(x)

=          cos(x)·[ 1 + cot2(x) ]                                         factor out the cos(x) term

=          cos(x)·csc2(x)                                                   replace 1 + cot2(x) with csc2(x)

=          cos(x)·[ 1 / sin2(x) ]                                          replace csc2(x) with 1/sin2(x)

=          [ cos(x) / sin(x) ]·[ 1 / sin(x) ]                            divide sin2(x) into its two factors

=          cot(x)·csc(x)                                                     replace ...

 Mar 18, 2020

8 Online Users